IMU Optimal Rotation Rates - Patrick Grates (IEEE Open Journal of Instrumentation and Measurement)
In the field of sensors and instrumentation used for navigation, rotation of the instruments and sensors has been used extensively in navigation systems to remove errors due to bias, bias instability, and noise. Microelectronic mechanical systems (MEMSs)-based inertial measurement units (IMUs) have been rotated at increasingly higher angular rates in the interest of managing and removing error from the system. The question becomes, “What is the ultimate rotation rate for a MEMS-based IMU to manage or remove error while retaining sensitivity for accurate measurements? This study delves into the nuances of IMU rotation rates, and what rotation rates are optimal for high-quality measurements. It explores the impact of rotation on the sensitivity of the accelerometers while obtaining stability in angular rate measurements from the gyros. Additionally, the study evaluates methods used for determining which rotation rates are best. The findings aim to enhance the performance of MEMS-based IMUs in dynamic environments and contribute to advancements in navigation systems used in autonomous vehicles and robots reliant on internal and independent systems.